Discourses of teacher quality in the Australian print media 2014–2017: a corpus-assisted analysis. Issue 6 (1st November 2020) - Mockler, Nicole
ABSTRACT: Discourses of 'teacher quality' have been on the rise in Australia since at least the standards-focused policy reforms of the 1990s. This paper uses a corpus-assisted analysis to explore recent deployments of 'teacher quality' and 'teaching quality' in the Australian print media, drawing on 432 articles collected from the 12 Australian national and capital city daily newspapers over the four-year period from January 2014 to December 2017. The analysis highlights that 'teacher quality' and 'teaching quality' are deployed differently in respect to school teachers and teachers in higher/vocational education contexts, and examines the nature of these differences. It demonstrates that the print media plays a key role in shaping and/or reflecting the links between discourses of teacher quality and notions of standards and accountability in education; and also in reflecting the highly politicised and political nature of teacher quality discussions and debates in Australia at this time.